The Use of Number Tower Media to Improve Intelligence Count Operation Ability in Deaf Students - Rohamah, Mamah (JASSI ANAKKU, 2021)
The purpose of this study was to determine the use of the Tower of Numbers media in improving the ability to count integer operations for deaf students. The research method used is classroom action research or abbreviated as CAR. The subjects in this study were 4 students with hearing impairments at the Special School, in Subang Indonesia. The results of using the Integer Tower media are very easy and helpful for students in solving math questions in addition and subtraction of integers with results below 15. It can be seen that the average result of the first cycle is 43.75, the second cycle is 56.67, and the third cycle is 66.67. There is an increase of 20.75% from cycle I to cycle III which indicates an increase in the ability to count integer operations through number tower media for deaf students. This is because using the Number Tower media makes it easier for students to complete arithmetic operations on integers. The number tower media is considered by teachers to be used in learning mathematics with integer arithmetic operations and can be used for normal students and students with special needs.